1998
DOI: 10.1021/es971118r
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Perchloroethylene by Surfactant-Modified Zeolite as Controlled by Surfactant Loading

Abstract: The sorption of nonpolar hydrophobic organic compounds by soil organic matter has long been attributed to a partitioning mechanism, with the sorption coefficient proportional to the fractional organic carbon content of the soil. However, deviations from this linear proportionality have been observed and reported in the literature by many authors. In our study a natural zeolite was modified with a cationic surfactant to achieve different fractional organic carbon contents and different surfactant molecule confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 27 publications
(50 reference statements)
10
114
0
4
Order By: Relevance
“…This observation has been attributed to differences in structure between sorbed and dissolved surfactant aggregates. Li and Bowman (1998) demonstrated that the perchloroethylene distribution coefficient on surfactant-modified zeolite is a function of CTMAB loading and resultant organic phase density. Perchloroethylene is most efficiently sorbed by surfactant-modified zeolite when the surfactant is present at or below full monolayer coverage.…”
Section: Sorption Of Ctmab On Bentonitementioning
confidence: 99%
See 1 more Smart Citation
“…This observation has been attributed to differences in structure between sorbed and dissolved surfactant aggregates. Li and Bowman (1998) demonstrated that the perchloroethylene distribution coefficient on surfactant-modified zeolite is a function of CTMAB loading and resultant organic phase density. Perchloroethylene is most efficiently sorbed by surfactant-modified zeolite when the surfactant is present at or below full monolayer coverage.…”
Section: Sorption Of Ctmab On Bentonitementioning
confidence: 99%
“…The distribution coefficients (K ss ) for sorbed surfactants were highest at low surfactant loadings, decreasing sharply as loading levels increased. Li and Bowman (1998) found that the sorption of perchloroethylene by a surfactant-modified zeolite was dependent on the configuration of the bound surfactant molecules, as well as on the fractional organic carbon content. Likewise, Sun and Jaffe (1996) found that the partitioning of phenanthrene into an adsorbed dianionic surfactant phase is generally 5-7 times more effective than into the same surfactant in water.…”
Section: Introductionmentioning
confidence: 99%
“…This can be understood by the mechanism of surfactant attachment on clay framework. It is well-known for a long time that surfactant modified clay or organoclay has the ability to adsorb and retain anionic compound [27][28][29]. Due to the molecular structure of cationic surfactant like CTAB that consists of two essential parts: (1) head positive group of quaternary ammonium and (2) hydrophobic tail of hydrocarbon chain (C16) and the capability of this surfactant to form micelles in the solution, the attachment of cationic surfactant on clay creates organic rich layer on the clay surfaces [16].…”
Section: Ccbs 2016mentioning
confidence: 99%
“…This barrier is actually a cross between chemical and biological methods, because the compost acts as a carbon source for microbial populations, which are active in the reduction of the chromium. Naturally occurring zeolite coated with cationic surfactants has also been investigated as an adsorbant for chromium in permeable reactive barriers (18).…”
Section: Aquitardmentioning
confidence: 99%